Old age – roleless role or time of freedom - Grotowska, Stella (Instytut Socjologii Uniwersytet Wrocławski, 2014)
Although today the aging of societies is a fact, it is not obvious which direction societies will take in facing the phenomenon. Most likely, the needs of elderly people will become more visible and social institutions will not stay indifferent and will provide help to those people in almost every area of life – business, work, social services (especially medical and educational), culture and religion.This paper is an attempt to analyse this process from the perspective of one of the elements of social structure, i.e. social roles. This analysis was to indicate the direction of the above-mentioned changes. Several roles were taken into consideration, namely that of a caregiver and a charge, a grandfather and grandmother, a member of a religious community, and a citizen.
Keywords: roleless role; social roles in old age; ageing of society; care in old age